Building Towards Better Learning: Evolution of Practical Design, Build and Test Activities in an Introductory Mechanical Engineering Design Course - Govender, Reuben; de Villiers, Adriaan (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
We describe the iteration of a practical design and prototype testing activity in our 2nd year Mechanical Design course. The initial implementation was a low complexity, low risk design task where only FDM 3D printing was used for manufacturing a static structural part. Subsequent implementations involved more complex design tasks, where prototypes required moving machine elements, and the manufacturing “toolkit” expanded to include LASER cutting and carpentry tools. We discuss challenges encountered, either due to logistical difficulties or poor estimation of student preparedness for workshop tasks. Our students have embraced the experience and we intend to retain this activity, noting some logistical and scheduling improvements that will facilitate future iterations.